The Potential Role of Gut Mycobiome in Irritable Bowel Syndrome - Gu, Yu; Zhou, Guoqiong; Qin, Xiali; Huang, Shumin; Wang, Bangmao; Cao, Hailong (Frontiers in Microbiology, 2019)
The human gut is inhabited by diverse microorganisms that play crucial roles in health and disease. Gut microbiota dysbiosis is increasingly considered as a vital factor in the etiopathogenesis of irritable bowel syndrome (IBS), which is a common functional gastrointestinal disorder with a high incidence all over the world. However, investigations to date are primarily directed to the bacterial community, and the gut mycobiome, another fundamental part of gut ecosystem has been underestimated. Intestinal fungi have important effects on maintaining gut homeostasis just as bacterial species. In the present article, we reviewed the potential roles of gut mycobiome in the pathogenesis of IBS, and the connections between the fungi and existing mechanisms such as chronic low-grade inflammation, visceral hypersensitivity and brain-gut interactions. Moreover, possible strategies targeted at the gut mycobiome for managing IBS were also described. This review provides a basis for considering the role of the mycobiome in IBS, and offer novel treatment strategies for IBS patients, moreover, add new dimensions to researches on microorganism.